Environmental impacts, management and potential recovery of residual sludge from the stone industry: The piedmont case. (March 2020) - Zichella, L.; Dino, G.A.; Bellopede, R.; Marini, P.; Padoan, E.; Passarella, I.
Abstract: The management of residual sludge from dimension stone processing activities (EWC 010, 413) represents a large concern for stone industry. Such sludges are characterised by a fine size distribution, high heavy metal contents and, potentially, TPH (Total Petroleum Hydrocarbon) contents. The objects of the present study are represented by gang-saw with abrasive shot (GSS), diamond frame-saw (DSS) and mixed (MS) sludges. The first one is high in Cr, Ni, Cu and TPH, the second presents high contents in Co, Cr and TPH, and the third represents a mix of the first two ones. Present legislation indicates that they can be disposed of in landfills or can be recovered (R5-R10) as filling material for environmental rehabilitation or as feeding materials for cement production. The sampled materials were obtained from the Verbano Cusio Ossola (VCO) and Luserna Stone quarry basins (Piedmont, Northern Italy). These materials were physically and chemically characterised, and magnetic separation was performed to rapidly evaluate the heavy metal contents in the sludge. Afterwards, three different experiments were carried out for environmental and civil applications. The first one, for substrate production, was carried out using GSS, DSS and MS from VCO area. The second one, for CLSM and plaster production, was performed on materials from VCO and Luserna stone quarry basins (CLSM using GSS from VCO and plaster using DSS from Luserna stone quarry basin). The results here reported are promising for the three applications. Highlights: Ornamental stone processing waste, management and recovery. Foresee the correct reuse, exploiting the intrinsic characteristics of the sawing sludge. Cost reduction and energy saving. Sawing sludge environmental application as substrate and civil application as plaster and CLSM.